National Accounts of Well-being - DIENER, Ed (Institutional Knowledge at Singapore Management University, 2012)
National accounts of subjective well-being should be used to assess the various facets of citizen’s well-being such as life satisfaction, trust in others, positive emotions, meaning and purpose in life, and engagement and interest. Although economic indicators have reigned within policy debates, the purpose of the economic indicators is ultimately to enhance “happiness”—subjective well-being. National measures of well-being that are collected systematically at periodic intervals will not only help focus attention on wellbeing as a major goal of societies, but can give information to leaders about policy alternatives, and thus inform policy debates in a way that complements economic analyses. Although global well-being measures such as life satisfaction are useful, measures that are focused on certain target populations, on current policy questions, and on specific activities and life domains often will be most informative for policy debates. Various concerns about national accounts of well-being are addressed.